The OPTIMIST study: optimisation of cost effectiveness through individualised FSH stimulation dosages for IVF treatment. A randomised controlled trial - van Tilborg Theodora C; Eijkemans Marinus JC; Laven Joop SE; Koks Carolien AM; de Bruin Jan; Scheffer Gabrielle J; van Golde Ron JT; Fleischer Kathrin; Hoek Annemieke; Nap Annemiek W; Kuchenbecker Walter KH; Manger Petra A; et al. (BMC, 2012)
Abstract Background Costs of in vitro fertilisation (IVF) are high, which is partly due to the use of follicle stimulating hormone (FSH). FSH is usually administered in a standard dose. However, due to differences in ovarian reserve between women, ovarian response also differs with potential negative consequences on pregnancy rates. A Markov decision-analytic model showed that FSH dose individualisation according to ovarian reserve is likely to be cost-effective in women who are eligible for IVF. However, this has never been confirmed in a large randomised controlled trial (RCT). The aim of the present study is to assess whether an individualised FSH dose regime based on an ovarian reserve test (ORT) is more cost-effective than a standard dose regime. Methods/Design Multicentre RCT in subfertile women indicated for a first IVF or intracytoplasmic sperm injection cycle, who are aged < 44 years, have a regular menstrual cycle and no major abnormalities at transvaginal sonography. Women with polycystic ovary syndrome, endocrine or metabolic abnormalities and women undergoing IVF with oocyte donation, will not be included. Ovarian reserve will be assessed by measuring the antral follicle count. Women with a predicted poor response or hyperresponse will be randomised for a standard versus an individualised FSH regime (150 IU/day, 225-450 IU/day and 100 IU/day, respectively). Participants will undergo a maximum of three stimulation cycles during maximally 18 months. The primary study outcome is the cumulative ongoing pregnancy rate resulting in live birth achieved within 18 months after randomisation. Secondary outcomes are parameters for ovarian response, multiple pregnancies, number of cycles needed per live birth, total IU of FSH per stimulation cycle, and costs. All data will be analysed according to the intention-to-treat principle. Cost-effectiveness analysis will be performed to assess whether the health and associated economic benefits of individualised treatment of subfertile women outweigh the additional costs of an ORT. Discussion The results of this study will be integrated into a decision model that compares cost-effectiveness of the three dose-adjustment strategies to a standard dose strategy. The study outcomes will provide scientific foundation for national and international guidelines. Trial registration NTR2657